2022
DOI: 10.1002/jcla.24818
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum anion gap and all‐cause mortality of unselected adult patients: A retrospective cohort study of >20,000 patients

Abstract: Background Even though the serum anion gap (AG) is frequently measured in clinical practice, there is not much research that has examined long‐term mortality in unselected adult patients. Our study's objective was to investigate how serum anion gap levels could be used to predict death in unselected participants. Methods The relationship between baseline serum AG levels and short‐, intermediate‐, and long‐term all‐cause mortality in unselected adult patients is examined using the Cox proportional risk analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“… 9 An elevated level of AG increases all-cause mortality in unselected adults. 10 Moreover, AG can predict short-time prognosis for cerebral infarction patients. 11 Although the specific mechanisms were not well understood and explained.…”
Section: Discussionmentioning
confidence: 99%
“… 9 An elevated level of AG increases all-cause mortality in unselected adults. 10 Moreover, AG can predict short-time prognosis for cerebral infarction patients. 11 Although the specific mechanisms were not well understood and explained.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies have suggested that there was a correlation between AG and the prognosis of surgical patients 26,27 . Recently, a study conducted on unselected adult patients suggested that higher levels of serum AG were positively associated with all‐cause mortality 28 . Furthermore, an increase in serum AG levels is correlated with an increased risk of patient mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 Recently, a study conducted on unselected adult patients suggested that higher levels of serum AG were positively associated with all‐cause mortality. 28 Furthermore, an increase in serum AG levels is correlated with an increased risk of patient mortality. It seems that AG is a highly promising indicator.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated associations in populations such as patients with cardiogenic shock, cardiac disease, post–cardiac arrest complications, disseminated intravascular coagulation, postoperative status, and advanced kidney disease. Ji and Peng demonstrated a positive correlation between serum anion gap values and all-cause mortality among unselected adult patients using only the MIMIC-III database [ 22 ]. While many studies have concentrated on specific patient groups and relied on single databases or a limited set of covariates, our research has delved into the association between the anion gap (including the corrected anion gap) and in-hospital mortality among general ICU patients.…”
Section: Discussionmentioning
confidence: 99%